Predicting response to Azithromycin therapy in asthma - Slater, Mariel (2015)
Macrolide antibiotics, including Azithromycin (AZM), can improve clinical symptoms in asthma regardless of infection status. Mechanisms underlying these beneficial effects are yet to be fully elucidated. Asthma is associated with a defective airway epithelium with reduced expression of structural proteins and aberrant repair responses. In vitro, AZM has shown anti-inflammatory and anti-viral actions, as well as enhancement of airway cell barrier integrity. Therefore, it was hypothesised that the beneficial effects of AZM in asthma may involve barrier reinforcement. The main aims were to determine the effects of AZM on airway epithelial function in vitro, in vivo and ex vivo.